High-parameter phenotypic characterization reveals a subset of human Th17 cells that preferentially produce IL-17 against M. tuberculosis antigen - Ogongo, Paul; Tran, Anthony; Marzan, Florence; Gingrich, David; Krone, Melissa; Aweeka, Francesca; Lindestam Arlehamn, Cecilia S.; Martin, Jeffrey N.; Deeks, Steven G.; Hunt, Peter W.; Ernst, Joel D. (Frontiers in Immunology, 2024)
Background. Interleukin 17 producing CD4 T cells contribute to the control of Mycobacterium tuberculosis (Mtb) infection in humans; whether infection with Human Immunodeficiency Virus (HIV) disproportionately affects distinct Th17 cell subsets that respond to Mtb is incompletely defined.Methods. We performed high-definition characterization of circulating Mtb-specific Th17 cells by spectral flow cytometry in people with latent TB and treated HIV (HIV-ART). We also measured kynurenine pathway activity by LC/MS on plasma and tested the hypothesis that tryptophan catabolism influences Th17 cell frequencies in this context.We identified two subsets of Th17 cells: subset 1 defined as CD4 + Vα7.2 -CD161 + CD26 + and subset 2 defined as CD4 + Vα7.2 -CCR6 + CXCR3 -cells of which subset 1 was significantly reduced in LTBI with HIV-ART, yet Mtb-responsive IL17-producing CD4 T cells were preserved; we found that IL17producing CD4 T cells dominate the response to Mtb antigen but not CMV antigen or staphylococcal enterotoxin B (SEB); and tryptophan catabolism negatively correlates with both subset 1 and subset 2 Th17 cell frequencies.Conclusions. We found differential effects of ART-suppressed HIV on distinct subsets of Th17 cells, that IL17-producing CD4 T cells dominate responses to Mtb but not CMV antigen or SEB, and that kynurenine pathway activity is associated with decreases of circulating Th17 cells that may contribute to tuberculosis immunity.